2013
DOI: 10.1088/0004-637x/776/1/6
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Fundamental Limitations to Statistical Detection of Redshifted H I From the Epoch of Reionization

Abstract: In this paper we explore for the first time the relative magnitudes of three fundamental sources of uncertainty, namely, foreground contamination, thermal noise and sample variance in detecting the Hi power spectrum from the Epoch of Reionization (EoR). We derive limits on the sensitivity of a Fourier synthesis telescope to detect EoR based on its array configuration and a statistical representation of images made by the instrument. We use the Murchison Widefield Array (MWA) configuration for our studies. Usin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
153
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 155 publications
(155 citation statements)
references
References 55 publications
2
153
0
Order By: Relevance
“…This relationship, known colloquially as "the wedge," was derived analytically (P12b; Vedantham et al 2012;Thyagarajan et al 2013;Liu et al 2014aLiu et al , 2014b, and has been confirmed in simulations (Datta et al 2010;Hazelton et al 2013) and observationally Dillon et al 2014). As described in P12b, the wedge is the result of the delay between when a wavefront originating from foreground emission arrives at the two antennas in a baseline.…”
Section: Calibrationmentioning
confidence: 70%
“…This relationship, known colloquially as "the wedge," was derived analytically (P12b; Vedantham et al 2012;Thyagarajan et al 2013;Liu et al 2014aLiu et al , 2014b, and has been confirmed in simulations (Datta et al 2010;Hazelton et al 2013) and observationally Dillon et al 2014). As described in P12b, the wedge is the result of the delay between when a wavefront originating from foreground emission arrives at the two antennas in a baseline.…”
Section: Calibrationmentioning
confidence: 70%
“…The reionization signals are of 10-100 mK brightness temperature, whereas the foregrounds are 100s to 10,000s of K; the spectral dynamic range required for the detection of the global EoR signature in any measurement of the absolute spectrum of the radio sky is about 10 3 -10 6 . It is therefore not surprising that considerable effort has been placed on the development of methods for the separation of the faint 21-cm signals from the substantially brighter foreground component in measurement data in the context of detection of both the global and statistical EoR signals (see, for example, Gnedin & Shaver 2004;Morales et al 2006;Vedantham et al 2012;Liu et al 2013;Thyagarajan et al 2013;Harker 2015;Bernardi et al 2016;Chapman et al 2016;Nhan et al 2017). …”
Section: Introductionmentioning
confidence: 99%
“…Datta et al 2010) show that the foreground contribution to the Cylindrical Power Spectrum P (k ⊥ , k ) is expected to be restricted within a wedge in the two dimensional (2D) (k ⊥ , k ) plane. The idea in Foreground Avoidance is to avoid the Fourier modes within the foreground wedge and only use the uncontaminated modes outside the wedge to estimate the 21-cm power spectrum (Vedantham et al 2012;Thyagarajan et al 2013;Pober et al 2014;Liu et al 2014a,b;Dillon et al 2014Dillon et al , 2015Ali et al 2015). In a recent paper Jacobs et al (2016) have compared several power spectrum estimation techniques in the context of MWA.…”
mentioning
confidence: 99%